Gender regimes, citizen participation and rural restructuring - Asztalos Morell, Ildikó; Bock, Bettina B. 1960- (Elsevier JAI, 2008)
This volume looks at the construction of gendered citizenship in different rural contexts. These contexts represent different welfare state and gender regimes, and different rural/agricultural conditions as characterized in different countryside types. This is a study of gender, citizenship and gender regimes, in a rural context with an international list of contributors.
Title from e-book title screen (viewed Mar. 11, 2008).
Keywords: Rural women -- Social conditions.; Sociology, Rural.; Sex role in the work environment.; Women in agriculture.; Local government -- Citizen participation.; Gender studies, gender groups.; Social Science -- Sociology -- Rural.; Social Science -- Gender Studies.; elektronické knihy; electronic books